1999
DOI: 10.1016/s0266-7681(99)90051-7
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Two Conservative Treatments for Ganglia of the Wrist

Abstract: This randomized prospective study assessed whether multiple puncture of the ganglion wall improves the results of simple ganglion aspiration. We found that 32% of ganglia resolved after aspiration alone in comparison with 22% after aspiration and multiple puncture. This difference was not significant. However, only 18% of patients requested formal surgical excision, suggesting that aspiration allays fears of malignancy and allows the patient to accept a minor cosmetic embarrassment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 6 publications
2
36
1
4
Order By: Relevance
“…Aspiration can be done on its own or combined with multiple punctures. Stephen et al (1999) found no difference in the recurrence rates between these two methods of treatment in a prospective randomised study of 92 patients. Aspiration may be combined with injection of various substances and Nelson et al (1972) published a recurrence rate of 35% to 60% following aspiration and injection of various substances into the ganglion.…”
Section: Article In Pressmentioning
confidence: 84%
“…Aspiration can be done on its own or combined with multiple punctures. Stephen et al (1999) found no difference in the recurrence rates between these two methods of treatment in a prospective randomised study of 92 patients. Aspiration may be combined with injection of various substances and Nelson et al (1972) published a recurrence rate of 35% to 60% following aspiration and injection of various substances into the ganglion.…”
Section: Article In Pressmentioning
confidence: 84%
“…2,3,15 Recurrence of the ganglion is the most frequently reported failure of any form of treatment and is believed to result from inadequate excision of the stalk. [3][4][5]11,18 The advent of wrist arthroscopy has provided surgeons with an alternative method of treatment for the symptomatic primary DG. Arthroscopic surgery offers advantages similar to those that have already been achieved for the larger joints of the body, namely the knee and shoulder.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Other than observation, nonoperative treatment such as closed rupture, ganglion puncture, and needle aspiration is associated with relatively higher rates of recurrence as high as 78%. [4][5][6] Surgical treatment with either open or arthroscopic excision is therefore offered with a lower risk of recurrence. Whereas open excision has historically been the traditional method of surgical treatment, [1][2][3]7 arthroscopic excision has been suggested as a potentially more favorable alternative.…”
mentioning
confidence: 99%
“…Given the evidence to support ultrasound as a diagnostic tool and the ease, cost, and lack of ionizing radiation exposure, the use of ultrasound-guidance in aspiration of these fluid collections should be considered as first-line therapy. Although a discussion of the optimal therapy for various ganglion and synovial cysts is beyond the scope of this review, there is some evidence to support the use of guided aspiration prior to or in lieu of surgical therapy [44] . For infectious indications, the use of ultrasound for both diagnostic and therapeutic purposes is also well described [45][46][47][48][49][50][51][52] .…”
Section: Fluid Collection Aspiration and Drainage Catheter Insertionmentioning
confidence: 99%